An Eulerian‐Eulerian Computational Approach for Simulating Descending Gas‐Liquid Flows in Reactors with Solid Foam Internals1. Issue 11 (19th September 2017) - Subramanian, Kumar; Zalucky, Johannes; Schubert, Markus; Lucas, Dirk; Hampel, Uwe
Abstract: Chemical reactors with new types of packings, such as metallic and ceramic open‐pore foams, have become subjects of scientific and engineering interest in the past decades. For trickle bed reactors, the new packing types provide favorable conditions, such as high specific surface area and low pressure drop, which are believed to contribute to an intensification of mass and heat transfer. Here, an attempt was made to model and predict the flow pattern and liquid distribution in a trickle bed reactor with solid foams, using computational fluid dynamics. A three‐dimensional model based on the relative permeability approach was adopted, where gas and liquid phases flow co‐currently downwards through a reactor with SiSiC ceramic foams as internals. The influence of both mechanical and capillary dispersion was included and studied in detail for foams of two different pore densities and for different initial distribution patterns. Abstract : A three‐dimensional computational fluid dynamics model based on a relative permeability approach was developed in order to simulate the flow through a reactor with ceramic foams as internals. The influence of capillary and mechanical dispersion forces on the liquid distribution was also discussed in detail. The results were validated against experimental data.